2020
DOI: 10.1002/job.2490
|View full text |Cite
|
Sign up to set email alerts
|

To be or not to be consistent? The role of friendship and group‐targeted perspective in managers' allocation decisions

Abstract: Summary Adopting a justice enactment perspective, we explore managers' consistent versus inconsistent application of existing rules in allocation decisions. We propose that when managers form friendship relationships with their employees, they are likely to experience greater tensions when fulfilling their managerial duties as resource allocators. On the one hand, managers may wish to deviate from the rules to benefit an employee who is also a friend. On the other hand, benefiting one employee (but not others)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 107 publications
(172 reference statements)
0
8
0
Order By: Relevance
“…An online questionnaire was prepared in Qualtrics and distributed through Prolific Academic (e.g., Derfler-Rozin et al, 2021 ) to managers of small and medium-sized family firms in the United States. The choice of the data collection method builds on the fact that online panel data has been increasingly used in recent years (Porter et al, 2019 ) while providing results that converge to conventional datasets in terms of data quality (Walter et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…An online questionnaire was prepared in Qualtrics and distributed through Prolific Academic (e.g., Derfler-Rozin et al, 2021 ) to managers of small and medium-sized family firms in the United States. The choice of the data collection method builds on the fact that online panel data has been increasingly used in recent years (Porter et al, 2019 ) while providing results that converge to conventional datasets in terms of data quality (Walter et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Future research should also examine how a supervisor's motives impact justice and fairness judgments within a group. For instance, it may be that a prosocially motivated supervisor violates rules of justice toward one employee to fulfill rules of justice toward another (cf., Derfler-Rozin et al, 2020). Indeed, research has suggested that feelings of empathy could lead those in authority to provide some employees with preferential treatment, though this effect tended to disappear when the decision-maker felt accountable to the group (Blader & Rothman, 2014).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…In the early modernist workplace, friendships were likely formed through mutual self-disclosure [21] and perceived similarity [22]. This likely took place in overtime work meetings, the "knock-off drinks," and the indirect or direct benefits attached to physical and proximal workplace connections (e.g., preferential application of existing rules [21]). Contemporary technologies affect this.…”
Section: Connectivitymentioning
confidence: 99%